Sleep and Phelan–McDermid Syndrome: Lessons from the International Registry and the scientific literature. Issue 10 (23rd August 2022) - Moffitt, Bridgette A.; Sarasua, Sara M.; Ward, Linda; Ivankovic, Diana; Valentine, Kathleen; Rogers, Curtis; Phelan, Katy; Boccuto, Luigi
Abstract: Background: Sleep is essential to maintaining a healthy life. Sleep disturbances among individuals with neurodevelopmental disorders are not well studied, affecting their early detection and treatment. Sleep disturbances in individuals with Phelan–McDermid Syndrome (PMS) are among the primary concerns reported by parents. However, little research has been aimed at addressing their concern. Methods: The purpose of this investigation was to identify and quantify specific sleep disturbances in people with PMS by analyzing data collected by the PMS Foundation International Registry. Results: The registry shows that 284 out of 384 (73.4%) individuals with confirmed chromosome 22q13 deletions or SHANK3 pathogenic variants have a sleep disturbance. The prevalence of sleep disturbances increases with age with 56% reporting a sleep disturbance in the 0–3 year age group and 90% reporting these disturbances in those over age 18 years old. The primary sleep disturbances were circadian rhythm sleep disorders that included difficulty falling asleep, frequent nighttime awakenings, difficulty returning to sleep after a nighttime awakening event, and hypersomnia and parasomnias including enuresis, night terrors, sleepwalking, and sleep apnea. Sleep disturbances were similarly frequent among individuals with SHANK3 pathogenic variants (84.8%) and those with deletions (71.9%), supporting the role of haploinsufficiency of SHANK3 in sleep. Conclusion: Sleep disturbances are a common feature of PMS and should be considered in clinical evaluation and management because of the effect they have on the quality of life of the patients and their families. Abstract : Sleep disturbances in individuals with Phelan‐McDermid syndrome (PMS) are a primary concern that is reported by parents and caregivers; however, research has yet to be aimed at addressing this concern. Our study aims to identify specific sleep disturbances and quantify the prevalence by analyzing the PMS International Registry. Sleep disturbances were present in 284 out of 384 individuals with PMS and frequencies were similar between individuals with SHANK3 pathogenic variants and those with deletions, supporting the role of haploinsufficiency of SHANK3 in sleep.